Methods to enhance the nonlinear optical frequency conversion in transition metal dichalcogenides - Vianna, Pilar Gregory (2022)
Since the isolation of graphene, an increasing number of 2D materials have been produced, attracting attention of researchers. Graphene, however, behaves as a zero-gap semiconductor, which limits its applicability in photonic and optoelectronic devices. 2D transition metal dichalcogenides (TMDs), on the other hand, can exhibit different phases, with tunable bandgap energy, enabling photonic applications including modulators, photodetectors, and lightemitting diodes. Furthermore, TMD monolayers present large nonlinear optical susceptibilities, which are responsible for effects such as second- and third-harmonic generation (SHG/THG), important for all-optical wavelength conversion. However, and despite the enormous number of benefits, direct TMD utilization for practical nonlinear optical applications is still an ongoing challenge. The atomic thickness of these materials results in reduced light–matter interaction, which naturally leads to low net frequency converted intensities (even if the conversion efficiency per unit thickness is higher than that in conventional materials). Therefore, ways to enhance the process and maximize the nonlinear interaction are crucial for making practical applications viable. In this work, we propose two different approaches for enhancing the nonlinear conversion efficiency in 2D TMDs. In our first strategy, we propose optimizing the overall system through the influence of the substrate. We demonstrate the use of fluorinedoped-thin-oxide (FTO) with an epsilon-near-zero point close to the pump wavelength to increase the nonlinear conversion efficiency in monolayer TMDs. Polarized SHG measurements reveal an intensity one order of magnitude higher on TMDs deposited on FTO than that on a bare glass substrate. Secondly, a promising alternative is to increase the lightmatter interaction length by integration of 2D materials in on-chip waveguides. We exploit an exfoliation method to obtain macroscopic single-crystal monolayers, comparable in quality to microscopic flakes, which can in principle be transferred to waveguide structures, opening a path to real photonic devices. Thus, we present the use of different techniques to manipulate 2D TMDs and propose the use of different substrates and platforms to obtain optimized and more efficient nonlinear optical responses.